2022
DOI: 10.1121/10.0016444
|View full text |Cite
|
Sign up to set email alerts
|

Effect of audio-tactile congruence on vibrotactile music enhancement

Abstract: Music listening experiences can be enhanced with tactile vibrations. However, it is not known which parameters of the tactile vibration must be congruent with the music to enhance it. Devices that aim to enhance music with tactile vibrations often require coding an acoustic signal into a congruent vibrotactile signal. Therefore, understanding which of these audio-tactile congruences are important is crucial. Participants were presented with a simple sine wave melody through supra-aural headphones and a haptic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 38 publications
2
27
0
Order By: Relevance
“…Due to the wide range of spectro-temporal variability and differences in the average frequency content of the tracks, this approach naturally came along with a lack of control with regards to the vibration stimulus, because we used the low-pass filtered audio signal to directly drive the vibration signal. Recent results (which we were not aware of at the time of designing the experiment) indeed suggest more effective approaches for deriving the vibration stimulus from the audio 19 . Furthermore, we here decided to use one fixed level of vibration in order to be able to interpret individual differences of vibrotactile effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the wide range of spectro-temporal variability and differences in the average frequency content of the tracks, this approach naturally came along with a lack of control with regards to the vibration stimulus, because we used the low-pass filtered audio signal to directly drive the vibration signal. Recent results (which we were not aware of at the time of designing the experiment) indeed suggest more effective approaches for deriving the vibration stimulus from the audio 19 . Furthermore, we here decided to use one fixed level of vibration in order to be able to interpret individual differences of vibrotactile effects.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the dimensions of a dissimilarity space derived from the ratings of normal-hearing listeners could be accurately modeled by a linear combination of audio and tactile stimulus features (attack time, roughness). Using simple sine wave melodies, it was further observed that time and intensity alignment are most critical for ratings of stimulus preference (used as a proxy of vibrotactile coherence) 19 . Frequency congruence was only observed to play a notable role for musician participants with frequency changes stretched by a factor of 1.5, suggesting a negligible role in terms of practical relevance.…”
Section: Introductionmentioning
confidence: 99%
“…Rhythm-the temporal relationship of events in a musical context-is arguably the first aspect to be discussed, as it is fairly well transmitted through tactile channels (Jiam and Limb, 2019). Substantial research has been dedicated to understanding the vibrotactile rhythm, investigating its impact on music aesthetics (Swerdfeger et al, 2009;Hove et al, 2019), and in regards to D/HOH individuals, its enhancement properties (Gilmore and Russo, 2020;Aker et al, 2022) as well as its interaction with the auditory counterpart (Lauzon et al, 2020). When it comes to pitch-the perceived (vibrotactile) frequencythe bandwidth is very limited compared to the ear, but this does not mean that humans cannot perceive pitch differences, only that the just noticeable difference between intervals must be larger, and the range is bound within 20 Hz-1,000 Hz (Chafe, 1993).…”
Section: Vibrotactile Music Augmentation-a Short Overviewmentioning
confidence: 99%
“…This translates to a lower level of robust synergy between the two sensory apparatuses that can be exploited to synthesize experiences impossible to achieve by unisensory means. Furthermore, research on auditory-tactile interactions has shown that tactile stimulus can influence the auditory stimulus and vice versa (Ro et al, 2009;Okazaki et al, 2012Okazaki et al, , 2013Aker et al, 2022). It can therefore be observed that auditory and haptic stimuli are capable of modifying or altering the perception of each other when presented in unison, as described by Young et al (2016) and Aker et al (2022), and studied extensively with respect to music experiences (Russo, 2019).…”
Section: Figurementioning
confidence: 99%
“…Specifically, the dimensions of a dissimilarity space derived from the ratings of normal-hearing listeners could be accurately modeled by a linear combination of audio and tactile stimulus features (attack time, roughness). Using simple sine wave melodies, it was further observed that time and intensity alignment are most critical for ratings of stimulus preference (used as a proxy of vibrotactile coherence) 22 . Frequency congruence was only observed to play a notable role for musician participants with frequency changes stretched by a factor of 1.5, suggesting a negligible role in terms of practical relevance.…”
Section: Introductionmentioning
confidence: 99%